Self Efficacy Dan Persepsi Iklan Pada Bungkus Rokok Dengan Motivasi Berhenti Merokok Pada Remaja Perokok Di Sma Negeri 4 Kabupaten Rejang Lebong - Putra, Aditya Yohandi; Handayani , Tita Septi; Sulastri, Sulastri (Utami Publisher, 2025)
Based on the percentage of countries with the largest tobacco producers in the world, Indonesia is in sixth place with a tobacco production of 136 thousand tons or around 1.91% of the world's total tobacco production. The number of smokers in the world reaches 2.8 billion people, where every year there are 5 million people who die from diseases caused by cigarettes. This study aims to determine the relationship between Self Efficacy and Perception of Advertising on Cigarette Packs with Motivation to Quit Smoking in Adolescents of SMA 4 Smokers in Rejang Lebong Regency in 2024. The method used is an analytical research design with cross sectional. The population in this study were male adolescents at SMA Negeri 4 Rejang Lebong, sampling using the random sampling method (random) of 55 students, using chi-Square analysis. The results of the study showed that out of 55 respondents, almost most of the respondents had Good Self Efficacy, most of the respondents had Good Perception of Cigarette Advertising, most of the respondents had Low Motivation to Quit Smoking. There is a significant relationship between Self Efficacy and Perception of Advertisements on Cigarette Packs with Motivation to Quit Smoking in Adolescent Smokers at SMA Negeri 4 Rejang Lebong Regency in 2024, (p=0.001, 0.034) (p=0.000). It is recommended for schools and guidance and counseling teachers to provide guidance to adolescent smokers in high school to avoid future health complications that can damage adolescent mindsets.